(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The present study, “Psychological Struggle of Parenting an Autistic Kid: A Study of Anita Nair’s Eating Wasps” gives a major insight into the sufferings of an Autistic or disabled child and how it reflects on the psyche of a mother. Mothers of children with severe autistic symptoms have higher levels of stress, anxiety, and depression than fathers. Autism though not a disease, it is a developmental disorder caused by differences in the brain. It is a complicated condition that includeproblems with communication and behaviour. This paper analyses the mother character and gives a deep insight intoher psychological ordeal with an autistic child. The analyses will also focus on thedifficult phases of the disabled, their family members and the influence of the environment on the autistic kid, Naveen.